Acupuncture Treatment of a Metatarsus Proximal End Fracture: A Case Report - Yılmaz Sezgin; Sinan Becel; Fatih Akçay (Medical Association of Pharmacopuncture Institute, 2016)
A tuberosity fracture is an avulsion fracture in an area 1.5 cm proximal to the fifth metatarsus. Six to eight weeks of immobilization may be required. A patient with a short leg plaster splint came to our clinic because of pain. The patient had a diagnosis of a fifth metatarsus fracture. Significant edema, fluctuation on the dorsolateral section of the left foot, and red color changes (0.2- to 0.3-cm diameter) on the skin of the anterolateral tibial area of the affected leg were noted. The locations of these skin changes corresponded to the GB34 (Yanglingguan) and the ST37 (Shanqiuxu) acupoints. The patient was successfully treated with acupuncture at these and several other acupoints. After 3 weeks (i.e., eight sessions), the patient returned to her routine life without any pain. This interesting case of metatarsus proximal end fracture shows that some acupoints may be visible during the progress of the disease. We used these acupoints in acupuncture treatment. Pain and edema were rapidly relieved, which may be attributable to the recovery of the lymphatic system in the affected area via acupuncture treatment.